Tren Pola Konsumsi Pembaca Media Cetak di Kalangan Mahasiswa di Kota Medan - Ginting, Rahmanita (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2015)
AbstractWe cannot imagine if there were no medla in the global information era. Sut when the media and infornn.ation expose the society that is not ready to accept it, the implication raises many new problems, is the print rnech will survive in the next 10-2Ci years into the future?" That is a common question that is often raised in discussions among the print rnedia publishers in recent years. sill Gates once predicted even the in 2000, the print rnedia will die. In fact till now still continueto exist. According to Baran rnedia influence on cultural audiences with a variety of ways. It is no wonder if our society today cannot be separated by the presence of communications media technology, Use of Internet technology in the print rnedia industry in the era of media convergence, on the one hand, is expected to increase the number of readers of var'iety of products produced by the company news print rnedia, On the other hand, it can also be counterproductive, that is rnost likely to trigger 2 drastic drop in circulation of various print media. Because many people think prefer to consume online media or digital paper (e-paper) which is ifree' and can be accessed frorn any location and at any time, rather than having to consurne print media should pay the subscription or Or retail costs. There is a change shift in the consumption pattern of print media readers. Accordingto McCluail mass media is the rnain power center point of overiap and influence ie between technology„ economics and politics, One strategy to stimulate grovvth of the print media - the advertising and circulation should start from a clear mapping of the print rnedia market potentiat in indonesia.